A igreja e o espírito da verdade em Hans Urs von Balthasar : um estudo do pensamento eclesiológico - Fernandes, Rafael Martins (2014)
This Master's dissertation, The Church and the Spirit of Truth in Hans Urs von Balthasar, aims to study and present the ecclesiological thought of Balthasar from the pneumatological perspective. Within the immense work of Balthasar, his main ecclesiological and pneumatological writings were selected for this study. At a first moment, the life, works and theological thought of this Swiss author are presented. It reveals that the center of its complex work is in the doctrine of the Trinity and the event Jesus Christ. Thought articulated in an innovative way, with the transcendentals. At a second moment, Balthasar's understanding of the Church is discussed. The Church is then presented from Christ and Mary, as a female person, placed in front of Christ and responding to him. The union of the images of the Church as body of Christ and spouse of Christ contribute to the clarification of this mystery. In them, the Church is understood as communion and mission. More specifically, as mystery of communion of people and missions in Christ, forming his personality. In this mystery, the figures of Mary, Peter and John stand out. Here, Peter personifies the ministry and the institution. Mary is the figure who represents the totality of the Church, with its maternal and espousal mission. At a third moment, the action of the Holy Spirit in this mystery of the Church is analyzed. For Balthasar, the Holy Spirit is fundamentally the Spirit "explainer" of the Truth of the Father − the incarnated Son. Then, in the Church, Son and Spirit act together. Still, the Spirit, which is poured into the Church with water and blood, in the event of Christ's death and resurrection, forces the Church to incarnate itself, testifying that love manifested in the cross. This "incarnating" work of the Spirit of the Church occurs in an objective and subjective way. The objectification of the Spirit takes place in the institutional mediations, as tradition, ministry, scripture and sacraments. The subjective mode of the Spirit acting in the Church is perceived in a special way in prayer, forgiveness and in the testimony of life. Balthasar, in this complex articulation, helps to better understand the joint work of the Trinity in the Church. It also offers a differentiated view of Church, dynamic, personalist, mysterious.